Cabinet’s Decree No. 39 of the Year 2025 Amending Certain Provisions of Cabinet’s Decree No. 47 of the Year 2020 Concerning the Rules, Controls and Procedures of Offering Heavy Industry Licenses and Others to Investors - Prime Minister (The Middle East Library for Economic Services, 2025)
Cabinet’s Decree No. 39 of the Year 2025 Amending Certain Provisions of Cabinet’s Decree No. 47 of the Year 2020 Concerning the Rules, Controls and Procedures of Offering Heavy Industry Licenses and Others to Investors